Fetal vitamin D concentration and growth, adiposity and neurodevelopment during infancy. Issue 10 (October 2018) - Wang, H; Yu, X.; Huang, L.; Chen, Q; Ouyang, F.; Wang, X; Zhang, J
Abstract Background/objectives To determine the association between cord blood 25-hydroxyvitamin D (25(OH)D) concentration with growth, adiposity and neurodevelopment during infancy. Subjects/methods Serum 25(OH)D was measured in cord blood by the liquid chromatography tandem mass spectrometry (LC-MS/MS) from the Shanghai's "Allergy and Obesity Cohort study" (n = 1244). Weight, length, head circumference, and body mass index (BMI)z -scores for age were calculated based on World Health Organization Standard (at 6 months, 1 years, and 2 years). Neurodevelopment was measured at 2 years using Ages and Stages Questionnaire. Generalized estimating equation and multivariable logistic regression model were exploited to examine associations between fetal 25(OH)D concentration and offspring outcomes. Results The median of the 25(OH)D concentration in cord blood was 22.4 ng/ml (interquartile range, 27.3–8.6). Infants born in winter had lower 25(OH)D concentration. 25(OH)D deficiency was not associated with weightz -score (mean difference, 0.07; 95% confidence internal (CI), −0.09 to 0.23), lengthz -score (mean difference, 0.01; 95% CI, −0.19 to 0.21), head circumferencez -score (mean difference, −0.06; 95% CI, −0.27 to 0.15) and BMI z-score (mean difference, 0.09; 95% CI, −0.07 to 0.25) or neurodevelopment during infancy, adjusting for sex, socio-economic position, pre-pregnancy maternal BMI, and maternal and neonatal characteristics. The associations did not vary by gender. A sensitivity analysis of available case analysis showed virtually the same results. Conclusions Fetal vitamin D concentration was not associated with growth, adiposity or neurodevelopment during infancy. The role of vitamin D concentration and its mechanistic pathway in the early origins of adiposity needs to be clarified.